THE JOURNALISTIC CODE OF ETHICS AND PROFESSIONALISM OF THE MEDIA - Austin Ernest Antariksa Tumengkol; Lia Anggia Nasution; Arianda Tanjung (Jurnal Ilmiah Ilmu Komunikasi Communique, 2021)
This research aims to examine the role of the Journalistic Code of Ethics for Journalists in Indonesia to form professionalism of the media, to examine the forming process of professionalism of the media and examine the application of the Journalistic Code of Ethics in Waspada Daily. In this study, the researcher uses the mass communication theory and professionalism of the media theory. Also, the researcher uses the interpretation of the Journalistic Code of Ethics for Journalists in Indonesia. This research uses descriptive methods to describe the problem based on the facts as it seems. The key informants in this research are the CEO, Editor-in-Chief, and some editors/journalists at the Waspada Daily. The result of this research is that Waspada Daily heavily needs to implement the Journalist Code of Ethics in order to form professionalism of the media as the guidelines for the journalists while performing their duties. This research also reveals the process of forming professionalism of the media in Waspada Daily that is not well functioned. Also it is discovered that the application of the Journalist Code of Ethics for Journalists in Waspada Daily is far from perfect considering many violations are being carried out as well.